Positive electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same
By incorporating a lithium excess oxide with a layered structure inside lithium composite oxide particles and a lithium manganese oxide with a spinel or layered structure outside, the positive electrode active material improves lithium ion mobility and structural stability, addressing cycle life and voltage drop issues in lithium secondary batteries.
Patent Information
- Application Number
- JP2023201270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2023-11-29
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-10-19
AI Technical Summary
Existing lithium secondary batteries face challenges with cycle life and voltage drop due to phase transitions during life cycling, particularly in lithium-nickel manganese cobalt oxide (Li(Ni) x Co y Mn z )O 2 materials.
The development of a positive electrode active material comprising lithium composite oxide particles with a layered lithium excess oxide structure inside and a lithium manganese oxide with a spinel or layered structure outside, creating a lithium and manganese concentration gradient to enhance lithium ion mobility and structural stability.
This solution increases the charge/discharge capacity, improves rate characteristics, and enhances the internal structure stability of the particles, thereby addressing the issues of cycle life and voltage drop in lithium secondary batteries.
Smart Images

Figure 0007665717000002 
Figure 0007665717000003 
Figure 0007665717000004
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same, which include lithium peroxide having a layered crystal structure inside lithium composite oxide particles, and having an excessive or deficient state of the concentration of lithium and the concentration of metal outside the particles.
Background Art
[0002] With the development of portable mobile electronic devices such as smartphones, MP3 players, and tablet PCs, the demand for secondary batteries capable of storing electrical energy has increased explosively. In particular, with the emergence of electric vehicles, medium and large-sized energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries is increasing.
[0003] In recent years, the most prominent material as a positive electrode active material is lithium nickel manganese cobalt oxide Li(Ni x Co y Mn z )O 2 (in this case, x, y, and z are the atomic fractions of independent oxide composition elements, respectively, 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, and 0 < x + y + z ≤ 1). This material has been actively studied and used as a positive electrode active material, and has the advantage of showing a high capacity because it is used at a higher voltage than LiCoO 2 , and has the advantage of being low in price because the Co content is relatively small. However, it has the disadvantages of poor rate capability and poor life characteristics at high temperatures.
[0004] Therefore, research is being conducted to apply a lithium-excess layered oxide showing a high reversible capacity, which surpasses existing Li(Ni x Co y Mn z )O 2 to a lithium secondary battery.
[0005] However, problems such as the decrease in discharge capacity (cycle life) and voltage decay that occur during life cycling are caused by the phase transition from a spinel-like structure to a cubic structure due to the movement of transition metals during life cycling. These problems must be solved for commercialization of lithium secondary batteries. Summary of the Invention [Problem to be solved by the invention]
[0006] To solve the above problems, the phase transition during life cycling is suppressed to increase the charge / discharge capacity and eliminate the problems of life degradation and voltage enhancement.
[0007] In addition, the lithium ion mobility is increased by a phase formed outside the layered lithium-excess oxide, thereby improving the rate characteristics.
[0008] In addition, compared to conventional polycrystalline lithium-excess oxides, the energy density is increased and the specific surface area of the particles is reduced, thereby improving the internal structural stability of the particles. [Means for solving the problem]
[0009] A positive electrode active material for a secondary battery according to an embodiment of the present invention comprises lithium composite oxide particles, and contains an excess lithium oxide having a layered crystal structure represented by Chemical Formula 1 inside the lithium composite oxide particles, and contains a lithium manganese oxide represented by Chemical Formula 2 below outside the lithium composite oxide particles, and when the ratio of the number of moles of lithium (Li) to the number of moles of all metals (M) excluding lithium is Li / M, the excess lithium oxide contained inside and the lithium manganese oxide contained outside have different Li / M values. [C1]rLi 2 MnO 3 (1-r)Li aNi x Co y Mn z M1 1-(x+y+z) O 2 (In the chemical formula 1, 0 < r ≤ 0.6, 0 < a ≤ 1, 0 ≤ x ≤ 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < x + y + z ≤ 1, and the M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Cu, In, S, B, and Bi.) [Chemical formula 2] Li b Mn p O q (In the chemical formula 2, 0.1 ≤ b / p ≤ 2.5 and 0 < q ≤ 15.)
[0010] In addition, for the positive electrode active material for a secondary battery according to an embodiment of the present invention, a lithium concentration gradient can be formed from the inside to the outside of the lithium composite oxide particles.
[0011] In addition, for the positive electrode active material for a secondary battery according to an embodiment of the present invention, a manganese concentration gradient can be formed from the inside to the outside of the lithium composite oxide particles.
[0012] In addition, a method for manufacturing a positive electrode active material for a secondary battery according to an embodiment of the present invention includes: forming precursor particles for forming the inside of the positive electrode active material; mixing the formed precursor particles and a lithium compound and performing a first heat treatment; dispersing the particles that have undergone the first heat treatment in distilled water or an alkaline aqueous solution to form a coating by introducing a manganese-containing compound; and mixing a lithium compound with the coated particles and performing a second heat treatment.
[0013] In addition, a secondary battery according to an embodiment of the present invention includes the positive electrode active material.
Advantages of the Invention
[0014] The positive electrode active material according to the embodiment of the present invention has an increased charge / discharge capacity, and the problems of life deterioration and voltage buildup are eliminated.
[0015] In addition, the lithium ion mobility is increased by the phase formed outside the layered lithium-excess oxide, improving the rate characteristics.
[0016] In addition, the internal structural stability of the particles is improved. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a diagram showing SEM images of positive electrode active materials according to comparative examples and examples of the present invention. [Diagram 2] FIG. 2 is a conceptual diagram of a positive electrode active material according to Example 1 of the present invention. [Diagram 3] FIG. 4 is a conceptual diagram of a positive electrode active material according to Example 2 of the present invention. [Figure 4] FIG. 2 is a diagram showing TEM images of positive electrode active materials according to comparative examples and examples of the present invention. [Diagram 5] FIG. 2 is a diagram showing the results of EDS analysis of a positive electrode active material according to an example of the present invention. [Figure 6] FIG. 2 is a diagram showing the results of XRD analysis of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 7] FIG. 1 is a diagram comparing the charge / discharge capacities of secondary batteries according to a comparative example and an example of the present invention. [Figure 8] FIG. 1 is a diagram comparing the charge / discharge capacities of secondary batteries according to a comparative example and an example of the present invention. [Figure 9] FIG. 11 is a diagram comparing overvoltages of secondary batteries according to a comparative example and an example of the present invention. [Figure 10] FIG. 1 is a diagram comparing rate characteristics of secondary batteries according to a comparative example and an example of the present invention. [Figure 11] FIG. 1 is a diagram comparing the capacity retention rates of secondary batteries according to a comparative example and an example of the present invention. [Figure 12] FIG. 11 is a diagram comparing voltage retention rates of secondary batteries according to a comparative example and an example of the present invention.
Mode for Carrying Out the Invention
[0018] Expressions such as "comprising" used in this specification should be understood as open-ended terms that encompass the possibility of including other components.
[0019] "Preferred" and "preferably" as used in this specification refer to embodiments of the present invention that can provide predetermined advantages under a predetermined environment, and are not intended to exclude other embodiments from the scope of the present invention.
[0020] The positive electrode active material according to an embodiment of the present invention includes lithium composite oxide particles, and the interior of the lithium composite oxide particles contains a lithium excess oxide having a crystal structure represented by the following Chemical Formula 1 as a layered structure. [Chemical Formula 1] rLi 2 MnO 3 ·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O 2 (In the Chemical Formula 1, 0 < r ≦ 0.6, 0 < a ≦ 1, 0 ≦ x ≦ 1, 0 ≦ y < 1, 0 ≦ z < 1, and 0 < x + y + z ≦ 1, and the M1 is at least any one or more selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B, Ge, Si, and Bi.)
[0021] The layered lithium excess oxide may be a solid solution phase in which a monoclinic structure of Li 2 MnO 3 and a rhombohedral structure of LiMO 2 are mixed. Further, the M may be at least any one or more selected from Ni, Co, Mn, and M1.
[0022] The layered lithium-excess oxide exhibited Li 2 MnO 3 A plateau due to the above phenomenon may appear.
[0023] The positive electrode active material may have a layered structure in which lithium atomic layers and metal atomic layers of Ni, Co, Mn, or M1 are alternately stacked with oxygen atomic layers interposed therebetween.
[0024] The planes constituting the layers of the layered structure of the positive electrode active material may have a crystal orientation perpendicular to the C-axis. In this case, the mobility of lithium ions contained in the positive electrode active material is improved, and the structural stability of the positive electrode active material is increased. When applied to a battery, the initial capacity characteristics, output characteristics, resistance characteristics, and long-term life characteristics may be improved.
[0025] When the ratio of the number of moles of lithium (Li) to the number of moles of all metals (M) excluding lithium is Li / M, Li / M inside the lithium composite oxide particles can be 1.1 to 1.6, 1.2 to 1.6, 1.3 to 1.6, or 1.4 to 1.5.
[0026] In Chemical Formula 1, the value of x may be greater than 0 and less than 0.5, greater than 0 and less than 0.4, greater than 0 and less than 0.3, greater than 0 and less than 0.2, or greater than 0 and less than 0.1.
[0027] In the above Chemical Formula 1, the value of y may be greater than 0 and less than 0.5, greater than 0 and less than 0.4, greater than 0 and less than 0.3, greater than 0 and less than 0.2, or 0.1 to 0.2.
[0028] For example, the ratio of the number of moles of manganese to the total number of moles of nickel (Mn / Ni) inside the lithium composite oxide particle may be 1-4.5, 2-4, or 3-4.
[0029] In the above Chemical Formula 1, M1 is at least one material selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Cu, In, S, B, Ge, Si, and Bi.
[0030] As a more preferred example, M1 may be a dopant that acts as a flux for growing the primary particles. Acting as a flux means that M1 may act as a dopant that increases the size of the primary particles.
[0031] More preferably, M1 may be at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W, which can increase the size of the primary particles and can be appropriately adjusted within a specific range. Also, most preferably, M1 may be at least one selected from Nb and Ta.
[0032] For example, the M1 may be included in an amount of 0.01 mol % to 3 mol %, more preferably 0.1 mol % to 1 mol %, based on the total amount of the lithium-excess layered oxide. If the dopant M1 included as a flux for inducing the growth of primary particles exceeds the range, the lithium composite oxide is produced in an excessive amount, which may cause a decrease in capacity and efficiency, while if the dopant M1 is less than the range, the effect of growing the primary particles may be insignificant.
[0033] The positive electrode active material according to the embodiment of the present invention includes a lithium manganese oxide represented by the following formula 2 outside the lithium composite oxide particles.
[0034] [C2]Li b Mn p O q (In the above formula 2, 0.1≦b / p≦2.5, 0 <q≦15である。)
[0035] For example, the b / p value, which means the Li / M value outside the lithium composite oxide particles, may be 0.1 to 0.9, more preferably 0.3 to 0.9, and more preferably 0.5 to 0.8.
[0036] In this case, the lithium manganese oxide is Li 4 Mn 5 O 12 Or LiMn 2 O 4 It could be.
[0037] As an example, the b / p value may be 1.8 to 2.5, and more preferably 1.9 to 2.1.
[0038] In this case, the lithium manganese oxide is Li 2 MnO 3 It could be.
[0039] In the present invention, the inside and outside are differentiated by coating the material so as to contain Mn and then adding Li to form an outside of lithium manganese oxide having a spinel crystal structure or a lithium-excess layered structure.
[0040] In the positive electrode active material according to the embodiment of the present invention, when the ratio of the number of moles of lithium (Li) to the number of moles of all the metals (M) excluding lithium is Li / M, the lithium excess oxide contained in the interior and the lithium manganese oxide contained in the exterior have different Li / M values.
[0041] Although the layered lithium-excess oxide has problems of cycle life and voltage decay during cycling, the rate characteristics can be improved by a phase formed by making the lithium concentration and metal concentration in an excess or deficiency state outside the lithium composite oxide particles.
[0042] In addition, it inhibits the dissolution of Mn from oxides rich in lithium and manganese, and inhibits the lattice change from the spinel phase to the rock-salt phase that occurs mainly on the surface of the positive electrode active material during cycling, thereby improving the life characteristics and suppressing the decrease in discharge capacity and voltage drop.
[0043] For example, the exterior of the lithium composite oxide particle may be deficient in lithium compared to the interior (FIG. 2).
[0044] For example, the Li / M in the interior of the lithium composite oxide particle may be 1.2 to 1.6, and the Li / M in the exterior of the lithium composite oxide particle may be 0.1 to 0.9. In this case, the exterior of the lithium composite oxide particle may have a spinel crystal structure.
[0045] In this way, the mobility of lithium ions can be increased by coating the surface of the 2D structure inside the lithium composite oxide particles with the lithium manganese oxide having a 3D spinel structure.
[0046] For example, the exterior of the lithium composite oxide particle may have more lithium than the interior (FIG. 3).
[0047] For example, the Li / M in the interior of the lithium composite oxide particle may be 1.2 to 1.6, and the Li / M in the exterior of the lithium composite oxide particle may be 1.8 to 2.5. In this case, the exterior of the lithium composite oxide particle may have a layered crystal structure.
[0048] In this way, by coating the exterior of the particles with lithium manganese oxide, which has a higher lithium concentration, the capacity of the coating layer is expressed, and the charge capacity and discharge capacity can be increased.
[0049] For example, the lithium composite oxide particles may form a concentration gradient in which the lithium concentration decreases or increases from the inside to the outside.
[0050] In the present invention, by coating so as to contain Mn and then adding Li, a concentration gradient can be formed while the exterior has a spinel crystal structure or a lithium-excess layered structure.
[0051] As an example, the molar concentration of manganese in the coating layer formed on the exterior of the lithium composite oxide particle may be different from the molar concentration of manganese in the interior of the particle.
[0052] For example, the manganese concentration may be lower in the exterior of the lithium composite oxide particles than in the interior.
[0053] For example, the manganese concentration may be higher in the exterior of the lithium composite oxide particles than in the interior.
[0054] For example, the lithium composite oxide particles may form a concentration gradient in which the manganese concentration decreases or increases from the inside to the outside.
[0055] For example, the lithium composite oxide particles may include secondary particles formed by agglomeration of primary particles.
[0056] As a more preferred example, a dopant acting as a flux is mixed with a lithium compound in the firing step and then heat-treated together, thereby controlling the size of the primary particles to be increased, thereby solving the problems of a decrease in discharge capacity and a voltage drop, and improving the density of the positive electrode active material.
[0057] For example, primary particles having a size of more than 300 nm and not more than 10 μm may be adjusted to 50 vol% to 100 vol%, 70 vol% to 100 vol%, or 100 vol% of the total primary particles contained in the secondary particles.
[0058] For example, primary particles having a size of more than 500 nm and not more than 10 μm may be adjusted to 50 vol% to 100 vol%, 70 vol% to 100 vol%, or 100 vol% of the total primary particles contained in the secondary particles.
[0059] For example, primary particles having a size of more than 1 μm and not more than 10 μm may be adjusted to 50 vol% to 100 vol%, 70 vol% to 100 vol%, or 100 vol% of the total primary particles contained in the secondary particles.
[0060] Here, the size of the primary particle means the maximum length of the particle.
[0061] The average particle size of the primary particles of the positive electrode active material may be adjusted to be greater than 500 nm and less than or equal to 10 μm, or to be in the range of 1 μm to 10 μm.
[0062] The secondary particles of the positive electrode active material may have an average particle size of 2 μm to 20 μm.
[0063] In this case, the average particle size may be defined as a particle size that corresponds to 50% of the cumulative volume in a particle size distribution curve.
[0064] As a more preferred example, the size of the primary particles is increased to increase the portion corresponding to the single crystal structure, and the more the portion corresponding to the single crystal structure, i.e., the fewer the number of primary particles, the more the voltage drop problem that occurs in polycrystals can be improved. In addition, by adjusting the size of the primary particles, the specific surface area of the positive electrode active material can be reduced, thereby eliminating the problem of side reactions with the electrolyte.
[0065] In the present invention, inducing the growth of the primary particles includes all of the concepts of nucleation, ostwald ripening, and particle aggregation.
[0066] For example, by adjusting the size of the primary particles through the addition and content adjustment of the dopant M1, the full width at half maximum (FWHM(deg.)) at I(104) in XRD analysis of the positive active material may be 0.1(deg.) to 0.25(deg.).
[0067] For example, by adjusting the size of the primary particles through the addition and content control of the dopant M1, the energy density per volume (Wh / L) of the positive active material may be 2.7 (Wh / L) to 4.0 (Wh / L).
[0068] For example, the size of the primary particles can be adjusted by adding and adjusting the content of the dopant M1, thereby increasing the specific surface area (BET, m 2 / g) is 0.01 (BET, m 2 / g)~2(BET,m 2 / g).
[0069] However, as the primary particles become larger, the lithium ion diffusion distance increases, which causes a problem of overpotential due to concentration polarization of lithium ions during charging and discharging. As a result, the kinetics decreases, and the capacity of the positive electrode active material may decrease. Therefore, the present invention can solve this problem by making the lithium concentration or metal concentration on the particle surface in an excess or deficiency state, or by forming a concentration gradient.
[0070] The method for manufacturing a positive electrode active material for a secondary battery according to an embodiment of the present invention includes a first step of forming precursor particles for forming the inside of the positive electrode active material.
[0071] The precursor particles may be formed by co-precipitation, spray-drying, a solid phase method, wet grinding, a fluidized bed drying method, or a vibration drying method, but is not limited thereto.
[0072] After the first step and before the second step, the method may further include a step of washing and drying the formed precursor particles.
[0073] Also, the method may further include a step of roasting the formed precursor particles at 300° C. to 600° C. after the first step and before the second step.
[0074] Next, after the first step, the method includes a second step of mixing the formed precursor particles with a lithium compound and performing a first heat treatment.
[0075] At this time, the first heat treatment temperature may be 700°C to 900°C.
[0076] As a more preferred example, the first heat treatment may further include mixing a compound containing M1 of Formula 1 and then heat treating the mixture.
[0077] Next, after the second step, the particles that have been subjected to the first heat treatment are dispersed in distilled water or an alkaline aqueous solution to form an exterior of the positive active material, and then a manganese-containing compound is added to coat the particles.
[0078] For example, the method may further include a step of washing with water and drying after the third step and before the fourth step.
[0079] Then, after the third step, a fourth step is included in which a lithium compound is mixed with the coated particles and a second heat treatment is performed.
[0080] At this time, the second heat treatment temperature may be 400°C to 700°C.
[0081] For example, after the fourth step, the steps of washing with water and drying can be further included.
[0082] A secondary battery according to an embodiment of the present invention includes the positive electrode active material.
[0083] The positive electrode active material is as described above, and the binder, conductive material, and solvent are not particularly limited as long as they can be used on a positive electrode current collector of a secondary battery.
[0084] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but is not particularly limited thereto as long as it can be used as a secondary battery.
[0085] Hereinafter, the positive electrode active material according to the embodiment of the present invention will be described in detail.
[0086] <Example 1> Lithium manganese oxide having a spinel structure is formed by deficienting lithium on the outside.
[0087] Internal synthesis Using the co-precipitation method, spherical Ni 0.2 Co 0.1 Mn 0.7 CO 3 The precursor was synthesized using NiSO in a 90 L reactor. 4 6H 2 O, CoSO 4 7H 2 O and MnSO 4 H 2 A 2.5M aqueous solution of a composite transition metal sulfate solution containing 20:10:70 molar ratio of NaCO and 25wt% NaCO was added. 3 and 28 wt% NH 4 The pH in the reactor was maintained at 10.0 to 12.0, and the temperature of the reactor was maintained at 45°C to 50°C. In addition, N 2 was added to the reactor to prevent the produced precursor from being oxidized. After the synthesis and stirring were completed, washing and dehydration were carried out using a filter press (F / P) equipment. Finally, the dehydrated product was dried at 120°C for 2 days and filtered through a 75μm (200mesh) sieve to remove 18μm and 4μm Ni particles. 0.2 Co 0.1 Mn 0.7 CO3 The precursor was obtained.
[0088] Roasting The precursor is placed in a box furnace. 2 Alternatively, the mixture was kept in an air (50 L / min) atmosphere, the temperature was increased at 2° C. per minute, and the firing temperature was maintained at 550° C. for 1 to 6 hours, after which the furnace was cooled.
[0089] First heat treatment Add LiOH or Li to the precursor to give a Li / M ratio of 1.45. 2 CO 3 was weighed out, and Nb was added as a flux dopant. 2 O 5 The mixture was mixed in a box furnace at 0.6 mol%. 2 Alternatively, the mixture was kept in an air (50 L / min) atmosphere, the temperature was increased by 2° C. per minute, and the firing temperature was maintained at 900° C. for 7 to 12 hours, followed by furnace cooling.
[0090] External Synthesis The surface of the sintered product was coated with 5 mol% Mn by co-immersion. The active material and distilled water were weighed out in a weight ratio of 1:2, the active material was dispersed in the distilled water, and then MnSO 4 H 2 A metal sulfate solution in which O was dissolved in distilled water was added. At this time, the pH was maintained at 10.0 to 12.0 using NaOH. After coating, washing and dehydration were performed using a filter press (F / P) equipment, and then it was dried at 150°C for 14 hours.
[0091] Second heat treatment Next, LiOH or Li is added to the wet-coated product so that the Li / Mn (coating amount) ratio becomes 0.5 to 0.8. 2 CO 3 After weighing, the mixture was mixed using a mixer. The mixture was then placed in a box furnace. 2Alternatively, the mixture was maintained in an air atmosphere, the temperature was increased at 4.4° C. per minute, and the firing temperature was maintained at 450° C. for 7 to 12 hours, followed by furnace cooling.
[0092] <Example 2> Excess lithium is placed on the outside to form a layered lithium manganese oxide.
[0093] In the second heat treatment step, LiOH or Li was added to the wet coating product so that the Li / Mn (coating amount) was 2.0. 2 CO 3 A positive electrode active material was prepared in the same manner as in Example 1, except that the second heat treatment was performed at 600° C. after weighing.
[0094] <Comparative Example> Does not form lithium manganese oxide on the outside. A positive active material was prepared in the same manner as in Example 1, except that the external synthesis and second heat treatment steps in Example 1 were not performed.
[0095] <Production Example> Manufacture of lithium secondary batteries 90 wt % of the positive electrode active materials according to the examples and comparative examples, 5.5 wt % of carbon black, and 4.5 wt % of PVDF binder were dispersed in 30 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was applied to a 15 μm-thick aluminum (Al) thin film as a positive electrode current collector, dried, and roll-pressed to prepare a positive electrode. The loading level of the positive electrode was 5.5 mg / cm. 2 and the electrode density is 2.3 g / cm 3 It was.
[0096] Metallic lithium was used as the counter electrode for the positive electrode, and 1M LiPF 6 , EC / DMC=1 / 1 (v / v) was used.
[0097] A separator made of a porous polyethylene (PE) film was interposed between the positive electrode and the negative electrode to form a battery assembly, and the electrolyte was injected to manufacture a lithium secondary battery (coin cell).
[0098] <Experimental Example> From the SEM analysis of FIG. 1, it can be seen that in the positive electrode active material according to the embodiment, the surface of the lithium-excess oxide particles having a layered structure in which the size of the primary particles has grown is uniformly coated with lithium manganese oxide.
[0099] 4, it can be confirmed that in the positive electrode active material according to Example 1, lithium manganese oxide having a spinel structure is formed on the surface of lithium-excess oxide particles having a layered structure.
[0100] The Line-EDS analysis in Figure 5 is a method for analyzing the change in metal concentration by applying a voltage to the particle surface, and it can be seen that a manganese concentration gradient is formed from the inside to the outside of the lithium composite oxide particles. It can also be seen that the Mn content on the surface is higher in Example 2 than in the Comparative Example.
[0101] From the XRD analysis of FIG. 6, it can be seen that lithium manganese oxide having a spinel structure was formed in the positive electrode material of Example 1.
[0102] 7, it can be seen that the positive electrode active material of Example 1 has an increased discharge capacity compared to the Comparative Example, because the 3D spinel coating on the 2D surface accelerates lithium ion mobility.
[0103] Referring to FIG. 8, it can be seen that the positive electrode active material of Example 2 has an increased charge capacity compared to the Comparative Example. This is because the Li 2 MnO 3 It can also be seen that not only the charge capacity but also the discharge capacity is increased.
[0104] 9, it can be seen that the positive electrode active material according to the embodiment of the present invention has a significantly reduced overvoltage compared to the comparative example, because the lithium ion conductivity is improved by the material coated on the surface.
[0105] 10, it can be seen that the positive electrode active material according to the embodiment of the present invention has improved rate characteristics compared to the comparative example, because the lithium ion conductivity is improved due to the material coated on the surface.
[0106] 11, it can be seen that the positive electrode active material according to the embodiment of the present invention has improved life characteristics compared to the comparative example, because the phase transition during cycling is mitigated by the material coated on the surface.
[0107] 12, it can be seen that the positive electrode active material according to the embodiment of the present invention has a suppressed voltage drop compared to the comparative example. This is because ... 2 MnO 3 This is because the lithium mobility was increased and the phase transition that occurred during cycling was mitigated.
[0108] The results of the above experiments are shown in Table 1 below. [Table 1]
Claims
1. Contains lithium composite oxide particles, The lithium composite oxide particles contain a lithium excess oxide having a layered crystal structure represented by the following Chemical Formula 1: The lithium manganese oxide represented by the following formula 2 is contained outside the lithium composite oxide particles: When the ratio of the number of moles of lithium (Li) to the number of moles of all metals (M) excluding lithium is Li / M, the lithium excess oxide contained in the interior and the lithium manganese oxide contained in the exterior have different Li / M values, M1 in the formula 1 includes at least one of Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W; Positive electrode active material for secondary batteries. [Chemical 1] rLi 2 MnO 3 ・(1 - r)Li a Ni x Co y Mn z M1 1-(x+y+z) O 2 (In the above Chemical Formula 1, 0<r≦0.6, 0<a≦1, 0≦x≦1, 0≦y<1, 0≦z<1, and 0<x+y+z<1; The M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Cu, In, S, B, Ge, Si, and Bi. [Chemical 2] Li b Mn p O q (In the above chemical formula 2, 0.1≦b / p≦2.5 and 0<q≦15.)
2. The positive electrode active material for secondary batteries according to claim 1 , wherein the lithium composite oxide particles have a lithium concentration gradient from the inside to the outside.
3. 2. The positive electrode active material for a secondary battery according to claim 1, wherein Li / M inside the lithium composite oxide particle is 1.1 to 1.
6.
4. 2. The positive electrode active material for a secondary battery according to claim 1, wherein Li / M outside the lithium composite oxide particles is 0.1 to 0.
9.
5. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the exterior of the lithium composite oxide particles has a spinel crystal structure.
6. 2. The positive electrode active material for a secondary battery according to claim 1, wherein Li / M outside the lithium composite oxide particles is 1.8 to 2.
5.
7. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the outer part of the lithium composite oxide particle has a layered crystal structure.
8. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the ratio of the number of moles of manganese to the number of moles of nickel (Mn / Ni) inside the lithium composite oxide particle is 1 to 4.
5.
9. The positive electrode active material for a secondary battery according to claim 1 , wherein the lithium composite oxide particles have a manganese concentration gradient from the inside to the outside.
10. The lithium composite oxide particles include secondary particles formed by aggregation of primary particles, 2 . The positive electrode active material for a secondary battery according to claim 1 , wherein M1 in Formula 1 is a dopant acting as a flux for growing the primary particles.
11. The method for producing a positive electrode active material for a secondary battery according to claim 1, forming precursor particles for forming an inner portion of the positive electrode active material; mixing the formed precursor particles with a lithium compound and performing a first heat treatment; dispersing the particles that have been subjected to the first heat treatment in distilled water or an alkaline aqueous solution to form an outer layer of the positive electrode active material, and then coating the particles with a manganese-containing compound; and mixing the coated particles with a lithium compound and performing a second heat treatment.
12. The method of claim 11, wherein the first heat treatment comprises further mixing a compound including M1 of Formula 1 and heat treating the mixture.
13. A secondary battery comprising the positive electrode active material of claim 1.
Citation Information
Patent Citations
Stabilized active material for lithium-ion batteries
WO2018137942A1